Implications of the Determination of Marriage Dispensation on Divorce Case : (Case Study at Sengkang Religious Court) - Takdir; Nur, Muhammad Tahmid; Abdullah, Muhammad Farhan (NAJAHA, 2022)
The purpose of this study is to discuss the implications of establishing a marriage dispensation for divorce cases at the Sengkang Religious Court. This type of research is qualitative field research with a normative juridical approach. A strategic solution to minimizing marital dispensation is to educate children that underage marriages have a high risk, including when giving birth later, the Regional Government must also play an active role by issuing regulations in the form of laws regarding dispensation of marriage and the prohibition of underage marriages. The implication of dispensation for underage marriage is a cause of conflict in the household which leads to divorce, besides that the cause of death of mothers or babies born is due to the lack of physical maturity on the part of the woman.